Precession aided magnetic stochastic resonance in ferromagnetic nanoparticles with cubic anisotropy - COFFEY, WILLIAM THOMAS; KALYMYKOV, YURI PETROVICH (American Physical Society, 2005)
It is shown that the signal-to-noise ratio in the magnetic stochastic resonance of single-domain ferromagnetic nanoparticles having cubic anisotropy exhibits a strong intrinsic dependence on the decay rate a of the Larmor precession. This dependence sprecession aided relaxationd is due to coupling between longitudinal relaxation and transverse sprecessionald modes arising from the lack of axial symmetry. It is most pronounced in the intermediate-to-low damping sKramers turnoverd region 0.1,a,1. The effect which does not exist for axially symmetric potentials may be used to determine a.
PUBLISHED
Keywords: Electronic & Electrical Engineering